Contingent self-worth and depression in early adolescents: The role of psychological inflexibility as a mediator - Kenichiro Ishizu; Tomu Ohtsuki; Yoshiyuki Shimoda (Acta Psychologica, 2022)
This study investigated whether lower psychological flexibility (psychological inflexibility) mediates the relationship between contingent self-worth and depressive symptoms among Japanese adolescents. A total of 210 Japanese junior high school students aged 12 to 15 years (106 boys and 104 girls) were recruited for this study. Participants completed the Japanese adaptations of the Self-Worth Contingency Questionnaire, the Avoidance and Fusion Questionnaire for Youth, and the Depression Self-Rating Scale for Children. Results indicated that psychological inflexibility mediated the association between contingent self-worth and depressive symptoms. Specifically, contingent self-worth affected lower psychological flexibility, which influenced higher depressive symptoms. The results highlight the importance of fostering autonomy and promoting psychological flexibility to reduce the risk of depression among adolescents.